A new species of Leptobrachella (Anura: Megophryidae) Smith, 1925 from Wuling Mountains in Hunan Province, China - Qian, Tian-Yu; Xia, Xin; Cao, Yue; Xiao, Neng-Wen; Yang, Dao-De (Zootaxa, 2020)
A new species of Leptobrachella, Leptobrachella wulingensis sp. nov. is described based on specimens collected from the Wuling mountains in Hunan Province, China. The new species can be distinguished from its congeners by a combination of having a SVL body size range of 24.5–32.8 mm in four adult males and 29.9–38.5 mm in three adult females; dorsal surface brown to reddish brown with indistinct markings; ventral surface creamy white, often with pale brown speckling on chest and margins; flanks with small to moderate black spots; skin on dorsum shagreened with sparse large warts, sometimes with short longitudinal ridges; toes with rudimentary webbing and narrow lateral fringes; dermal ridges under toes interrupted at the articulations; and iris bicolored with a bright orange or golden upper half, fading to silver in the lower half. Uncorrected sequence divergence between L. wulingensis sp. nov. and homologous 16S rRNA sequences available for all known species in the genus are ≥ 2.3%–2.9%.